Peperomia calcicola (Piperaceae), a new species from limestone outcrops of the southeastern Brazilian Atlantic Forest - Marcusso, Gabriel Mendes [UNESP] (2020)
Peperomia calcicola is here described as a new species from the Atlantic Forest of São Paulo state, southeastern Brazil. The species was found on limestone outcrops in the understory of rainforest in the Alto Ribeira State Tourist Park (PETAR). It is characterized by the unique combination of pilose to pubescent stems and leaves, the leaves 7-9-nerved, slightly discolorous, ovate to large lanceolate blades with acute apex and cordate to rounded base, and the spadix of 0.5-1.7 cm long. Here we present description, color photos, and taxonomic comparisons with the morphologically close taxa.